VILLAGE HEAD AND MOTIVATION OF PERGAM VILLAGE, RUPAT DISTRICT, BENGKALIS REGENCY - Jelika, Rozan; Effendi, Nahar (Jurnal Administrasi Publik : Public Administration Journal, 2020)
This study aims to describe the leadership of the village head in increasing the work motivation of village officials. This research was inspired by the improvement of the performance of village officials in Pergam Village, Rupat District, Bengkalis Regency. The research method used was descriptive qualitative approach. Data collection techniques with observation and documentation interviews. The problems that affect namely; A leader has a great influence in increasing employee motivation through his leadership, work motivation has a significant effect on employee performance. After reviewing the researchers found that the leadership of the village chief plays a role in increasing the work motivation of village officials. The efforts made by the Headman in increasing the apparatus' work motivation by doing; Headman's leadership in improving welfare, Headman's leadership in creating a harmonious work atmosphere, Headman's leadership in rewarding achievements, Headman's leadership in providing justice, Headman's leadership in respecting and involving the apparatus, Headman's leadership in completing work facilities, Headman's leadership in developing the potential of the apparatus , Village chief in creating strict and fair punishment.